A Drama Textbook with Sociodrama Method: Research and Development in Linguistic Education Study Program in Central Java - Evy Tri Widyahening (Intelektual Pustaka Media Utama, 2013)
This research was aimed to determine: (1) the quality of drama textbook which is used in Study Program of Language Education in Private Universities in Central Java; (2) how the development of drama textbook with sociodrama method; (3) the effectiveness of drama textbook with sociodrama method which have been developed by sociodrama.